WAYS TO INCREASE PROJECT EFFICIENCY THROUGH HUMAN CAPITAL DEVELOPMENT (International journal of artificial intelligence, 2025)
The article analyzes the structural elements of human capital and their impact on project efficiency, identifies existing problems and proposes effective solutions. The scientific novelty of the article lies in the systematic study of the relationship between project management and human capital, and also provides recommendations for its implementation in real practice in the modern conditions of the economy of Uzbekistan.